小児の下顎骨に発生した大きな集合性歯牙腫の1例 - 多田, 美里; 太田, 耕司; 武知, 正晃; 二宮, 嘉昭; 植月, 亮; 福井, 暁子 (日本口腔外科学会雑誌, 2019)
An odontoma is an odontogenic tumor composed of enamel, dentine, and cementum and is usually less than 20 mm in diameter. The World Health Organization classification divides odontomas into complex and compound. In previous reports from Japanese institutions, only two cases of compound odontoma arising in the mandible and greater than 30 mm in diameter have been reported. We describe a large compound odontoma arising in the mandible of a child.　A 6-year-old girl was referred to our hospital for evaluation of a radiopaque area on the left side of the mandible. Radiographic and computed tomographic examinations showed a large, circumscribed, radiopaque lesion, which measured 30 × 22 × 20 mm and was surrounded by a thin radiolucent area accompanied by an impacted tooth. Several small tooth-like structures were noted within the lesion. An odontoma was clinically diagnosed, and the tumor and impacted tooth were surgically removed by an intraoral approach with the patient under general anesthesia. The resected tumor was covered by a thin capsule and consisted of many small tooth-like structures. The histopathological diagnosis was a compound odontoma. The postoperative course was satisfactory, and we are continuing periodic follow-up examinations of the patient.